Anserobilharzia gen. n. (Digenea, Schistosomatidae) and redescription of A. brantae (Farr & Blankemeyer, 1956) comb. n. (syn. Trichobilharzia brantae), a parasite of geese (Anseriformes) - Brant, Sara V.; Jouet, Damien; Ferte, Hubert; Loker, Eric S. (Zootaxa, 2013)
A new genus, Anserobilharzia, is proposed to accommodate Anserobilharzia brantae n. comb. (syn. Trichobilharzia bran-tae Farr & Blankemeyer, 1956), a species of avian schistosome thus far found exclusively in anserini geese (Anser, Branta, Chen) from Europe and North America, and Gyraulus snails. Recent collections and subsequent molecular analyses showed that A. brantae was distinct from Allobilharzia and Trichobilharzia and grouped basal to Trichobilharzia. Using nuclear 28S, ITS and mitochondrial cox1 as genetic yardsticks, samples of A. brantae from North America and Europe were each other’s closest relative and distinct from Allobilharzia and Trichobilharzia. Anserobilharzia brantae was also distinct when compared morphologically with other species of closely related avian schistosomes. The following descrip-tion is based on males, females, eggs, and cercariae. The new genus is characterized by a) ovoid egg (72–145μm x 44– 89μm) with spine, b) male with >500 testes and caecal reunion anteriad to seminal vesicle, c) cercariae with 5+1 flame cells, and d) intermediate hosts are planorbid snails. The only confirmed species of snail host is Gyraulus parvus in North America. Based on presented data, we propose a new genus and new combination for A. brantae justified by morpholog-ical, host use, and molecular characteristics.